A cross-sectional study on immunization status among Anganwadi children in a rural community, Karnataka - Dr. Dhananjaya C.D.; Dr. Sunil B.N. (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Communicable diseases are the major cause of morbidity and mortality in children. One of the most costeffective methods for well-being of a child is immunization. In India, immunization services are offered through anganwadis which is mainly well utilized in rural areas. The Universal Immunization Programme which was launched in 1985 currently covers Ten Vaccine Preventable diseases in Karnataka. In spite of good resources the immunization rate remains low in some areas because of various reasons.Objectives: To assess the immunization coverage of 3-6 years children coming to Anganwadis.Materials and Methodology: The present study was carried out in rural field practice area of a medical college in Kolar district. In this descriptive cross sectional study, children in the age group of 3-6 years who were enrolled with anganwadi were listed and their mothers were interviewed by using a pre-tested semi-structured questionnaire which captured various sociodemographic details, factors favoring and obstacles for immunization was Captured for a period of 6 months from October 2018 to March 2019.Results: Completely immunized children were 86 %, partially immunized were 14 % and none was un-immunized. The most common reasons for not immunizing the child were Current Illness for the Child, Time and Place not known for vaccination and Fear of Side Effects, Mother’s education, Social class and Religion were significantly associated with Immunization.Conclusion: The overall coverage of immunization among the rural area was good but emphasis on addressing the reasons for partial immunization should be met by effective IEC and Inter-personal communication. The reasons for partial/non immunization are preventable and may be increased by creating awareness about vaccine preventable disease and strengthening the immunization services.